Two new polyporoid species of Fomitopsidaceae (Polyporales, Basidiomycota) from India - Saha, Rituparna; Dutta, Arun Kumar; Roy, Anirban; Acharya, Krishnendu (European Journal of Taxonomy, 2024)
Two new species of Fomitopsidaceae, Pseudofomitopsis fusca R.Saha, A.K.Dutta & K.Acharya sp. nov. and Fomitopsis benghalensis R.Saha, A.K.Dutta & K.Acharya sp. nov., are described from West Bengal, India, based on morphological and molecular phylogenetic analyses (nuclear ITS sequence). Pseudofomitopsis fusca sp. nov. possesses perennial, triquetrous to ungulate, sessile basidiocarps with a shiny, glabrous, azonate, dark brown upper surface, a yellowish grey pore surface with angular pores (3–5 per mm), a dimitic type of hyphal system with clamped generative hyphae, fusoid cystidioles; ellipsoid, cotton blue positive, and basidiospores 3–5 × 1.5–3.5 µm. Fomitopsis benghalensis sp. nov. is characterized by its annual, resupinate basidiocarp with pilose, bluish white to orange-grey, warty, woody upper surface, bluish-white pore surface, circular to angular pores (5–7 per mm), a trimitic type of hyphal system with clamped generative hyphae, fusoid cystidioles, and cylindrical to elongate basidiospores (5.5–8 × 2.5–3.5 µm). The new taxa are compared to closely related taxa. Photomicrographs of the basidiocarps, along with detailed morphological descriptions and a molecular sequence-based phylogenetic tree, are provided.